Investigation on influences of initial residual stress on thin-walled part machining deformation based on a semi-analytical model - Gao, Hanjun; Zhang, Yidu; Wu, Qiong; Li, Bianhong (Journal of materials processing technology, 2018)
[Display omitted] The manufacturing accuracy of the thin-walled parts is significantly affected by the residual stress in the blank and the resulting machining deformation. In recent years, the prediction and control of the machining deformation have received extensive attentions. A semi-analytical machining deformation prediction model is proposed for the thin-walled parts in terms of the equivalent bending stiffness calculated by finite element method (FEM) simulation and theory of plates and shells. Machining deformations of seven typical study cases are predicted by the semi-analytical model. Corresponding experiments and FEM simulations are conducted to validate the proposed model. Then, the influences of the initial residual stress and equivalent bending stiffness on the machining deformation are investigated based on the quantitative results of the proposed model, which is difficult to be obtained by the previous FE models. The results suggests that 1) improving the bending stiffness of the part can effectively reduce the machining deformation; 2) decreasing the stresses in the top part of the blank and in the length direction is more advantageous to reduce the deformation than other parts and directions; 3) the final machining deformation is basically determined by the residual stress within a certain thickness under the blank surface when the residual stress symmetrically distributes along the mid-plane in thickness direction.